The effect of extracellular vesicles derived from oral squamous cell carcinoma on the metabolic profile of oral fibroblasts - Lipka, Aleksandra; Søland, Tine M.; Nieminen, Anni I.; Sapkota, Dipak; Haug, Trude M.; Galtung, Hilde K. (Frontiers in Molecular Biosciences, 2025)
IntroductionOral cancer is one of the most common forms of head and neck cancers. Oral squamous cell carcinoma (OSCC) accounts for more than 90% of the oral malignancies. The molecular pathogenesis of OSCC is complex as it involves altered expression of specific genes and proteins, but also comprises changes in metabolic processes. It is suggested that extracellular vesicles (EVs) released by cancer cells may contribute to cancer development and metastasis by recruiting and changing phenotype of normal cells that surround the tumor.MethodsThe aim of the project was to characterize the effect of OSCC EVs on the metabolic profile of normal oral fibroblasts (NOFs). Targeted liquid chromatography mass spectrometry metabolic profiling was performed on control cells and NOFs exposed to OSCC EVs for 24 and 48 h.ResultsAnalysis of detected metabolites revealed that OSCC EVs affected NOFs the most after 24 h of exposure. Among metabolites that were significantly altered at 24 h, pyruvate, ATP, UTP, coenzyme A, and dihydroxyacetone phosphate were upregulated, while fatty acids such as nervonic acid, linoleate, oleate, palmitoleic acid, and docosahexaenoic acid were downregulated. These findings were supported by Western blotting of pyruvate kinase M2 (PKM2) and aldolase, fructose-bisphosphate A (ALDOA).ConclusionThe metabolic pathways of glycolysis, citric acid cycle, and amino acid metabolism were enriched, suggesting that OSCC EVs cause phenotype switch in NOFs that may contribute to acquiring a pro-tumorigenic phenotype.